PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Sekretariat DPRD Kabupaten Subang) - Widilestariningtyas, Ony; Azijah, Salmah Nur (JEMBA, 2023)
Good governance is a form of success in carrying out the task of building the country in accordance with the goals that have been planned. This triggered a phenomenon where the strengthening of public demands for transparency as well as the accountability of financial management both central and regional with the realization of the delivery of financial statements. This study aims to 1) find out how much influence the competence of human resources has on the quality of regional financial statements 2) find out how much influence the application of the regional financial accounting system has on the quality of regional financial statements. The research uses quantitative methods by describing the results of questionnaires and verifiability techniques to analyze the data that has been collected. Using primary data sources of survey data collection techniques. The population is 30 employees of the DPRD Secretariat. Samples were taken by saturated sampling technique. The data were processed using SPSS by multiple linear regression analysis methods. The results of the study concluded that 1) the competence of human resources affects the quality of local government financial statements 2) the implementation of the regional financial accounting system affects the quality of local government financial statements.